Adaptation of the Novel into the Romance of the Three Kingdoms Series (1994) (Universitas Pendidikan Indonesia, 2026)
Adaptation is a common phenomenon in the world of cinematography, and one of the most frequently used sources for adaptation is historical novels. As one of the classic Chinese novels, Romance of the Three Kingdoms has been adapted into various media, such as theater performances, films, and television series. Across these adaptations, different portrayals can always be found—whether in terms of narrative, history, or culture. As a result, the reception of each adaptation varies. This study aims to examine how the novel is portrayed in its 1994 adaptation. A qualitative research method with a descriptive approach is used, paired with the theory of ekranisasi (film adaptation theory), to identify the types of modifications that occur. The results show that although many modifications are present, these changes are made carefully without compromising the essence of the original novel.